Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1086/513901
|View full text |Cite
|
Sign up to set email alerts
|

Familial Skewed X Inactivation: A Molecular Trait Associated with High Spontaneous-Abortion Rate Maps to Xq28

Abstract: We report a family ascertained for molecular diagnosis of muscular dystrophy in a young girl, in which preferential activation (> or = 95% of cells) of the paternal X chromosome was seen in both the proband and her mother. To determine the molecular basis for skewed X inactivation, we studied X-inactivation patterns in peripheral blood and/or oral mucosal cells from 50 members of this family and from a cohort of normal females. We found excellent concordance between X-inactivation patterns in blood and oral mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
119
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 39 publications
4
119
0
1
Order By: Relevance
“…The absence of positive transmission results suggests that skewing is determined, at least in part, by post-XCI selection biases, some of which may be transmissible. Accordingly, a number of studies performed in non-neonatal populations have demonstrated a certain degree of heritability of skewing (65)(66)(67). In light of these considerations, we propose that neonatal skewing is caused in part, but not exclusively, by selection biases operating after primary XCI.…”
Section: Figurementioning
confidence: 91%
See 2 more Smart Citations
“…The absence of positive transmission results suggests that skewing is determined, at least in part, by post-XCI selection biases, some of which may be transmissible. Accordingly, a number of studies performed in non-neonatal populations have demonstrated a certain degree of heritability of skewing (65)(66)(67). In light of these considerations, we propose that neonatal skewing is caused in part, but not exclusively, by selection biases operating after primary XCI.…”
Section: Figurementioning
confidence: 91%
“…Skewing of XCI was also reported in rare cases of balanced X/autosome translocations, which perturbed the normal mechanisms of XCI (10). Furthermore, skewing has been associated with some complex traits such as recurrent abortion (11) and mental retardation (12), although the causative role of skewing in these situations has not been established. Skewing is a common feature of tumorigenic processes in which an acquired somatic mutation occurs in a single progenitor cell that subsequently undergoes clonal expansion and gives rise to progeny with the same XCI pattern (13,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They further demonstrated that affected individuals have a large segment of DNA deleted in the Xq28 region. 49 Further evidence for a genetic cause of NRXI came with the recent work by Plenge et al 50 who documented a rare cytosine to guanine mutation in the XIST (X-inactivation specific transcript) minimal promoter in nine females of two different families that all showed preferential inactivation of the X chromosome carrying the mutation.…”
Section: Figurementioning
confidence: 99%
“…These results suggested an X-linked transmission of NRXI in this family. Pegoraro et al 49 reported a high incidence of NRXI in a family and localized the genetic anomaly responsible for the trait to the Xq28 region using linkage analysis. They further demonstrated that affected individuals have a large segment of DNA deleted in the Xq28 region.…”
Section: Figurementioning
confidence: 99%